ANALYSIS OF WORK ACCIDENTS DURING THE PLUMBING INSTALLATION PROCESS USING THE FAULT TREE ANALYSIS METHOD - Bastuti, Sofian; Alfatiyah, Rini (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2024)
The plumbing installation process often harbors potential risks that can lead to workplace accidents. Considering the serious consequences of workplace accidents both in terms of health and economy, there are six types of workplace accidents in the plumbing installation process: foot crushed by a pipe, hand cut by a cutting tool blade, eyes exposed to welding smoke, burnt by hot welding slag, sparked by friction between iron and a cutting blade, and leg scratched by the edge of a pipe. This study aims to analyze workplace accident incidents during the plumbing installation process using the Fault Tree Analysis (FTA) method with the hope of identifying the root causes of the accidents and formulating recommendations to improve work safety. The FTA method allows for the development of a systematic model that illustrates the cause-and-effect relationships of system failures and their components. The primary advantage of using FTA is its ability to provide a comprehensive understanding of complex accident scenarios by breaking them down into simpler basic events. The novelty of this research lies in its application of FTA specifically to the plumbing installation process, which has not been extensively explored in previous studies. The results identified that the cause of eyes exposed to welding fumes led to 11 basic events, while the mocus analysis revealed 7 basic events with 11 failure combinations.